Cooperativity in spin crossover materials as ligand's responsibility – investigations of the Fe(ii) – 1, 3-bis((1H-tetrazol-1-yl)methyl)bicyclo[1.1.1]pentane system. Issue 16 (6th April 2018) - Knoll, Christian; Müller, Danny; Seifried, Marco; Giester, Gerald; Welch, Jan M.; Artner, Werner; Hradil, Klaudia; Reissner, Michael; Weinberger, Peter
Abstract : In [Fe(ppditz)3 ]X2, X = BF4 −, ClO4 −, PF6 − spin crossover complexes the observed cooperativity originates only from the rigidity and internal strain of the ligand. Abstract : Criteria for a technologically relevant spin crossover (SCO) material include temperature and abruptness. A series of Fe(ii ) – 1, 3-bis((1 H -tetrazol-1-yl)methyl)bicyclo[1.1.1]pentane SCO complexes with various anions (BF4 −, ClO4 −, and PF6 − ) designed using a structure–property based concept is reported. All complexes feature abrupt SCO-behavior with T 1/2 between 170 K and 187 K. These materials demonstrate that without stabilizing the effects of incorporated solvents or a hydrogen bond-network, the observed cooperativity during high-spin–low-spin transition is anion independent and originates only from the rigidity and internal strain of the propellane-moiety in the ligand. Spectroscopy and structural investigations of these materials are supported by quantum chemical calculations.